2015
DOI: 10.1155/2015/836105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Osteoclast-Like Giant Cells: Report of the Seventh Case in the Literature

Abstract: Hepatocellular carcinoma with osteoclast-like giant cells is extremely rare, and only six cases have been previously reported. Its histogenesis is at the moment controversial. The authors report a case of hepatocellular carcinoma with osteoclast-like giant cells found in a 74-year-old woman. The patient came with a dull pain in the right upper abdominal quadrants due to a liver neoplasm described at CT scan. A wedge resection of the fifth hepatic segment with appendectomy, omentectomy, and debulking of the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…They are not present in normal tissues other than bones. Nevertheless, similar cells have been found in tumors of pancreas (Abid and Gnanajothy, 2019;Njoumi et al, 2014;Sah et al, 2015;Togawa et al, 2010;Bauditz et al, 2006), liver (Bauditz et al, 2006;Dioscoridi et al, 2015;Ikeda et al, 2003;Kuwano et al, 1984;Rosai, 1990), skin (Goel et al, 2011;Al-Brahim and Salama, 2005;Jiménez-Heffernan et al, 2018;Houang et al, 2015), lung (Nakahashi et al, 1987;Matsukuma et al, 2014;Lindholm et al, 2019;Kong et al, 2015;Dahm, 2017), breast (Stewart and Mutch, 1991;Agnantis and Rosen, 1979;Fadare and Gill, 2009;Ginter et al, 2015;Ohashi et al, 2018), and in many other tumors. Osteoid and bone formation was found in different cancers, such as breast cancer and melanoma (Hoorweg et al, 1997;Dekkers et al, 2019) These tumors can be considered as degenerated or more severely defected forms of teratomas/teratocarcinomas.…”
Section: Tumor Phenotypic Heterogeneitymentioning
confidence: 58%
“…They are not present in normal tissues other than bones. Nevertheless, similar cells have been found in tumors of pancreas (Abid and Gnanajothy, 2019;Njoumi et al, 2014;Sah et al, 2015;Togawa et al, 2010;Bauditz et al, 2006), liver (Bauditz et al, 2006;Dioscoridi et al, 2015;Ikeda et al, 2003;Kuwano et al, 1984;Rosai, 1990), skin (Goel et al, 2011;Al-Brahim and Salama, 2005;Jiménez-Heffernan et al, 2018;Houang et al, 2015), lung (Nakahashi et al, 1987;Matsukuma et al, 2014;Lindholm et al, 2019;Kong et al, 2015;Dahm, 2017), breast (Stewart and Mutch, 1991;Agnantis and Rosen, 1979;Fadare and Gill, 2009;Ginter et al, 2015;Ohashi et al, 2018), and in many other tumors. Osteoid and bone formation was found in different cancers, such as breast cancer and melanoma (Hoorweg et al, 1997;Dekkers et al, 2019) These tumors can be considered as degenerated or more severely defected forms of teratomas/teratocarcinomas.…”
Section: Tumor Phenotypic Heterogeneitymentioning
confidence: 58%
“…Generally, pleomorphic tumor cells lack cohesiveness and do not show a distinct trabecular pattern. Pleomorphic cells are common in poorly differentiated tumors (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…17 It was reported that RANKL expression might be associated with the induction of OGCs in some tumors with OGCs. 5,7,20 Therefore, we first examined the protein expression of RANKL and M-CSF in pulmonary adenocarcinoma with OGCs, and we found out that mononuclear cells showed immunopositivity for M-CSF, although focal. These findings suggest that the production of M-CSF might promote the differentiation or induction of OGCs, which is a similar microenvironment of bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…OGCs in the neoplastic tissues were reported to be derived from tumor‐associated macrophage through alternative pathway associated with vascular endothelial growth factor and matrix metalloproteinase 12, but it is also well known that RANKL and M‐CSF served as vital regulators of OGC differentiation and activation in bone marrow . It was reported that RANKL expression might be associated with the induction of OGCs in some tumors with OGCs . Therefore, we first examined the protein expression of RANKL and M‐CSF in pulmonary adenocarcinoma with OGCs, and we found out that mononuclear cells showed immunopositivity for M‐CSF, although focal.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation